What factors underlie associative and categorical memory illusions? The roles of backward associative strength and inter-item connectivity - Knott, Lauren M.; Dewhurst, Stephen A.; Howe, Mark L. (American Psychological Association, 2012)
Factors that affect categorical and associative false memory illusions were investigated in 2 experiments. In Experiment 1, backward associative strength (BAS) from the list word to the critical lure and interitem connectivity were manipulated in Deese-Roediger-McDermott (DRM) and category list types. For both recall and recognition tasks, the likelihood of producing DRM and category false memories was greater for lists with high BAS and low interitem connectivity. In Experiment 2, DRM and category lists with high BAS showed similar indirect priming effects in a word stem completion task. With low BAS, category lists, unlike DRM lists, showed no priming effect. We discuss the role of BAS, interitem connectivity, and associate-level differences in implicit and explicit measures of false memory production. © 2012 American Psychological Association.
Batch 005. Output ID 37712.
Keywords: DRM paradigm; False memories; Backward associative strength; Indirect priming; Category lists